A study on safety performance of construction sites for a safer working environments / Muzzammil Mohamed Ayob - Mohamed Ayob, Muzzammil (Faculty Architecture, Planninng and Surveying, 2015)
Construction remains one of the most dangerous industry where improvements to health and safety is deemed important. Safety is the most important aspect that needs to be taken into account on the construction site. The research assessed the safety and health performance of the construction sites and identifies the causes of accidents in construction sites. The case study for the research are construction sites in Klang Valley. The safety and health performance of the sites were assessed and the causes of accidents are identified. The research are based on the literature review and semi structured interview. The findings reveals the safety and health performance of the construction site and the common causes of accidents in construction sites. Recommendation of mitigation measures were made to improve the performance of the construction site in Klang Valley